2017
DOI: 10.4028/www.scientific.net/kem.742.602
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Carbon Fibers in Complex Structural Parts - Organic Sheets Made of rCF Staple Fiber Yarns

Abstract: In order to sustainably establish carbon fiber reinforced polymer composites (CFRPC) in the market on an industry scale, solutions on how to recycle these new materials have to be developed. Quasi-continuously aligned carbon staple fiber structures in organic sheets made of recycled carbon are one approach which will be dealt with in this article. The process chain as well as the mechanical properties will be presented. Moreover, the specific feature of staple fiber yarns to be able to plastically deform under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 1 publication
(1 reference statement)
0
10
0
Order By: Relevance
“…[30][31][32][33][34] Staple fiber organic sheets made of rCF have been developed based on rCF yarns, providing comparable but not yet equal material properties as virgin CF organic sheets. 35 In Longana et al, 36 the high performance discontinuous fiber process was applied in order to align rCF for the production of epoxy-based prepregs which also provide close to vCF values in terms of mechanical performance. By considering a second recycling loop, values significantly decreased by $20%.…”
Section: State Of the Art: Recycling Of Cfsmentioning
confidence: 99%
“…[30][31][32][33][34] Staple fiber organic sheets made of rCF have been developed based on rCF yarns, providing comparable but not yet equal material properties as virgin CF organic sheets. 35 In Longana et al, 36 the high performance discontinuous fiber process was applied in order to align rCF for the production of epoxy-based prepregs which also provide close to vCF values in terms of mechanical performance. By considering a second recycling loop, values significantly decreased by $20%.…”
Section: State Of the Art: Recycling Of Cfsmentioning
confidence: 99%
“…The hybrid yarns find their applications as woven fabrics, 34 knitted fabrics 35 and organic sheets 36 for thermoplastic composites as well as heating elements in lightweight applications. 37 So far, the development of hybrid yarn structures consisting of discontinuous CF and thermoplastic fibres has been explored based on wrap spinning , 36,[38][39][40][41] roving frame [42][43][44][45] and DREF-3000 friction spinning [46][47][48] machines. The pioneer work on the use of reclaimed CF to manufacture hybrid yarns by wrap spinning reported by Akonda et al [38][39] showed that the tensile strength of composites manufactured from waste CF fabric prepregs was found to be very low (maximum 160 MPa).…”
Section: Introductionmentioning
confidence: 99%
“…Current research is concentrating on recycling routes with aligned rCF, such as manufacturing of aligned mats, wovens, and noncrimp fabrics (NCF) for organic sheets. 12,21,[32][33][34][35][36][37][38] Recycling of CFs for high-performance materials is strongly in focus. The aim of this article is to introduce CFs as long and as aligned as possible into new structures.…”
Section: Introductionmentioning
confidence: 99%
“…This fact is taken into consideration in current research projects. 18,20,21,[40][41][42][43] In addition to developments on rCF yarns, efforts are also being made to process the fibers into oriented slivers and tapes. [44][45][46] Pickering et al, 7 Allen, 8 Turner et al, 9 Palmer et al, 10 Hofmann et al, 11 and Pickering et al 12 Low to medium Low to medium Automotive semistructures, equipment housings, and aircraft interiors Compression molding of aligned nonwovens, veils, and mats Geiger, 13 Turner et al, 14 Howarth et al, 15 Wong et al, 16 and Pickering et al 17 Medium Medium Automotive noncritical structures, aircraft interiors, and wind turbine noncritical structures Compression molding of wovens, NCF Hengstermann et al, 18,19 Abdkader et al, 20 and Goergen et al 21 Medium to high Medium to high Automotive structures NCF: non-crimp fabrics; rCF: recycled carbon fiber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation